Shear capacity investigation of steel-concrete composite girders in hogging moment regions. (July 2022) - Men, Pengfei; Zhou, Xuhong; Ye, Jiating; Di, Jin; Qin, Fengjiang
Abstract: Slender steel-concrete composite girders are commonly used in bridge structures; however, the influences of web shear-buckling and concrete slabs on the shear strength of these girders have rarely been investigated thus far. In this study, an experimental and numerical investigation was condcuted to determine the ultimate shear strength of slender composite girders in hogging moment regions. Six simply-supported composite girders and a bare-steel girder were experimentally subjected to combined negative moment and shear. In addition, the influences of the moment/shear ratio, web height–thickness ratio, concrete slab thickness, and web aspect ratio on the failure modes, web elastic buckling loads, ultimate loads, and web out-of-plane deformations of composite girders were investigated. Moreover, a nonlinear finite element (FE) model was developed and verified using the experimental results, and the verified FE model was used to conduct the parametric analysis. The results revealed that the shear strength of the composite girders in hogging moment regions increased linearly with the thickness, longitudinal reinforcement ratio, and width of the concrete slab, among which the slab thickness posed the greatest effect, followed by the reinforcement ratio, and lastly, the slab width. Furthermore, an equation was proposed based on the web shear-buckling and the concrete slab shear contribution to express the shear strength of composite girders in hogging moment regions. Conclusively, the proposed equation was validated with the experimental and numerical results. Highlights: Shear strength of slender composite girders in hogging moment regions is studied. A 3D nonlinear finite element model is developed and validated using tests results. Shear strength increases linearly with thickness, width, and rebar ratio of slab. A new equation for shear strength of slender composite girders is proposed. Effects of web shear-buckling and the concrete slab are considered in the equation.